Humanistic Higher Education in the Digital Age: The Proposal of Participatory Seminars at the School of General Studies of the University of Costa Rica - Monge Ortiz, Jorge Alberto (2025)
This article presents Participatory Seminars at the School of General Studies at the University of Costa Rica as an essential aspect of the comprehensive professional development of young people in the digital age.  In the theoretical approach, the paper uses the theories of authors such as Yuval Harari, Martha Nusbaum, and Salvador Pániker within the currents of neo-humanism in the 21st century. It concludes that Participatory Seminars are essential insofar as they constitute the comprehensive training necessary for students graduating from the University of Costa Rica.